Custodial reindeer and custodial goats - part of reindeer herding and animal husbandry - Evjen, Bjørg (Rangifer, 2009)
The Sami husbandry has traditionally incorporated reindeer, which did not belong to the nomadic household. According to the national census from 1875, this system was found in many parts of Norway. Among the counties, Nordland stood out having the highest number of households owing custodial reindeer. Most of the households were non-Sami, and most of them having less than ten reindeer. Especially in Nordland and Troms, a system with custodial goats also served as the transaction. There were eventually, with an exception of Finnmark, rules in place trying to prevent settled people from keeping reindeer, only followed in part. The system went on till after the Second World War, mainly because it was an important part of the household economy of the settled people. The great changes and rationalization within the agricultural sector, the growth of industrial society, and the modernisation of society in general undermined the use of reindeer as a part of the household livestock. Abstract in Norwegian / Sammendrag: Sytingsrein og sytingsgeiter, del av det samme husdyrholdet Systemet med sytingsrein har trolig foregått så lenge det har eksistert reindrift, det vil si at en del av reinflokken har bestått av dyr som tilhørte de bofaste, men som ble passet på av reindriftssamer. Kilder viser at systemet fantes over hele Norge der det ble drevet reindrift, men i størst utstrekning i Troms og Nordland. Sytingsgeiter kunne være en gjenytelse der reindriftssamenes geiter ble passet av de bofaste gjennom vinteren. Fra myndighetenes side ble det fra ca. 1900, med unntak av for Finnmarks del, satt inn restriksjoner for å begrense sytingsreinholdet. Det ble ikke uten videre fulgt, da systemet hadde stor betydning for både nomader og de bosatte. Moderniseringen av samfunnet etter andre verdenskrig førte imidlertid til at dette utbyttet mistet sin betydning, og sytingsreininstitusjonen ble tilsynelatende borte, men er nå delvis lovlig igjen fra 2007.